Journal of African Languages and Linguistics (De Gruyter Mouton, 1979)
The Journal of African Languages and Linguistics was founded in 1979 and has established itself as an important refereed forum for publications in African linguistics. The journal welcomes original contributions on all aspects of African language studies, synchronic as well as diachronic, theoretical as well as data-oriented.